Clinical efficacy of intravenous immunoglobulins for the treatment of dermatomyositis skin lesions without muscle disease. (1st August 2013) - Bounfour, T.; Bouaziz, J.‐D.; Bézier, M.; Cordoliani, F.; Saussine, A.; Petit, A.; Juillard, C.; Bagot, M.; Rybojad, M.
Abstract Background Treating dermatomyositis (DM) with isolated skin involvement is difficult and inconsistently performed. Intravenous immunoglobulins (IVIg) are recommended for corticoresistant or corticodependant DM, but only a few cases of IVIg use in DM with isolated skin involvement have been reported. Design We performed a retrospective monocentric study of 27 patients who were treated with IVIg for severe DM skin lesions (no or minor muscle involvement) after failure of photoprotection and at least one line of treatment. Results Nineteen patients (70%) exhibited a major response, four patients exhibited a partial response and four patients exhibited no response, including two patients with grade 3 side effects (headaches). The mean number of IVIg courses was 4.8 (range 1–15). Ten patients (53%) relapsed, with a median time of 6.2 months after the last IVIg course. Six of these patients were successfully treated with a new IVIg course. Muscle disease developed in six patients. Conclusion IVIg may be an effective and safe treatment for DM with isolated skin involvement. Relapse occurred frequently, but treatment with a new course of IVIg was successful. Controlled studies are required to confirm these results.